A Practical Implementation Fire Monitoring Systems Using Fuzzy Methods - Dea Ummul Khabibah; Kenzi Dewandaru; Muhammad Tsabit; Silva Dimas Surya Permana; Yana Nurrohman; Agung Prayudha Hidayat; Dwi Yulinar Chairunisa (Batrisya Education, 2024)
Fires are serious disasters that require effective monitoring or control systems to identify risks and respond quickly. In this study, observations were made on the A Practical Implementation Fire Monitoring Systems Using Fuzzy Methods using temperature input from DHT22 sensors, smoke from MQ-2 sensors, and fire history as evaluation variables. The system will classify the temperature as